Sequence of the genes for tRNACys and tRNAAsp from spinach chloroplasts. - Holschuh, K (1983)
We have determined the map location and primary structure of two fragments of spinach chloroplast DNA which encompass the genes for tRNACysGCA and tRNAAspGUC. Identification of the genes for these two RNA species is based on the sequence of their anticodon triplets and on a comparison of the sequences with those of the equivalent tRNAs from Escherichia coli. Each gene occurs only once on the spinach chloroplast genome and neither contains an intervening sequence. Hybridization of the restriction fragments carrying these genes to chloroplast tRNA showed that both genes are transcribed in vivo.